A Nice Radical Equation | Algebra | Math Olympiad Prep

preview_player
Показать описание
A Nice Radical Equation | Algebra | Math Olympiad Prep

Get ready for a thrilling algebra challenge with this intriguing radical equation! Perfect for Math Olympiad preparation, this problem will test algebraic skills and problem-solving abilities. Join us as we break down the steps to solve this challenging equation, offering tips and tricks along the way.

Whether you're a student preparing for a math competition or a math enthusiast looking for a fun challenge, this video is for you. Don't forget to like, share, and subscribe for more math challenges and solutions. Let's dive into this radical equation together!

We'll cover:

Key concepts and definitions
Common pitfalls and how to avoid them
Detailed example problems with solutions
Tips and tricks to solve these equations efficiently

Additional links:

00:00 Introduction
00:21 Substitution
03:45 Solving cubic equation
05:42 Synthetic division
06:25 Quadratic formula
11:02 Discriminant
11:40 Solutions
12:12 Verification

Additional Resources:


#algebrachallenge #radicalequations #mathproblems #mathchallenge #problemsolving #algebra #education #mathematics #matholympiad

Join us and boost your problem-solving skills to ace the Math Olympiad & other competitive examinations! Don't forget to like, subscribe, and hit the notification bell for more math tips and tutorials.

Thank You for Watching!
Рекомендации по теме
Комментарии
Автор

The equation simplifies to 2x^6 -15x^4 -14x^3 +75x^2 -76 =0. By inspection, x=-1 is a solution. [2x^6 -15x^4 -14x^3 +75x^2 -76]/(x+1) = 2x^5-2x^4-13x^3-x^2+76x-76. Again, 2x^5-2x^4-13x^3-x^2+76x-76=0 has x=2 as a solution. These are the two valid solutions.

kprdqvg
Автор

(x² + y²) * x = 5x and (x² + y²) * y = 5y So xy(y+x) + 7 = 5(x+y) and (x+y)² = x² + y² + 2xy So you get (x+y) and xy faster

TrinityRed
Автор

7 - x³ = u³
5 - x² = u²

x³ + u³ = 7
x² + u² = 5

(x + u)(x² + u² - ux) = 7
(x + u)(5 - ux) = 7

x + u = 1
xu = -2

t² - t - 2 = 0
(t + 1)(t - 2) = 0

*x = -1* => u = 2
*x = 2* => u = -1

I think there are other roots. Maybe.

SidneiMV
Автор

Θετω 7-χ^3=y^3 αρα χ^3+y^3=7 και χ^2+y^2=5 κλπ

nyjfist